Art and science as creative catalysts - Gates-Stuart, Eleanor; Nguyen, Chuong; Adcock, Matt; Bradley, Jay; Morell, Matthew; Lovell, David (MIT Press, 2016)
Science, Art and Science Art collaborations are generally presented and understood in terms of their products. The authors argue that the process of Science Art can be a significant—perhaps the principal—benefit of these collaborations even though the process may be largely invisible to anyone other than the collaborators. Hosting the Centenary of Canberra Science Art Commission at the Commonwealth Scientific and Industrial Research Organisation (CSIRO) has shown the authors that while Science and Art pursue orthogonal dimensions of creativity and innovation, collaborators can combine these directions to access new areas of imagination and ideas.